1971
DOI: 10.1037/h0030365
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic reinforcement: A socioeconomic leveler.

Abstract: Sixty first-grade children from two different socioeconomic levels were presented a concept-acquisition problem after either 0, 6, or 12 trials of random reinforcement. The overall performance of the high-socioeconomiclevel children was superior to the low-socioeconomic-level children, but the results also indicated a significant interaction between socioeconomic level and number of random reinforcements. With an increase in the number of random reinforcements, the behavior of the high-socioecenomic-level chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…A similar phenomenon has been shown in laboratory studies using human subjects (e.g., Hiroto & Seligman, 1975), prompting a number of theorists to propose learned helplessness as a model or mechanism for a variety of failures of human adaptation in which passivity is present, such as failure in school (Dweck & Reppucci, 1973), stagnation of the lower class (Bresnahan & Blum, 1971), death of the institutionalized (Langer & Rodin, 1976), and so on. Best known of these applications is Seligman's (1974) suggestion that learned helplessness is at the core of reactive depression.…”
Section: Learned Helplessness: Application To Victimssupporting
confidence: 53%
“…A similar phenomenon has been shown in laboratory studies using human subjects (e.g., Hiroto & Seligman, 1975), prompting a number of theorists to propose learned helplessness as a model or mechanism for a variety of failures of human adaptation in which passivity is present, such as failure in school (Dweck & Reppucci, 1973), stagnation of the lower class (Bresnahan & Blum, 1971), death of the institutionalized (Langer & Rodin, 1976), and so on. Best known of these applications is Seligman's (1974) suggestion that learned helplessness is at the core of reactive depression.…”
Section: Learned Helplessness: Application To Victimssupporting
confidence: 53%
“…Furthermore, there is one experiment wherein environmental chaos was manipulated that strongly implicates the essential role of chaos in attenuating the poverty and task persistence relation. When reinforcement was contingent upon performance in a concept formation paradigm, high SES first graders outperformed their low‐SES peers (Bresnahan & Blum, ). However, when reinforcement was random, task performance was equally low for both SES groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of the covariation between poverty and child development is mediated by chaos (Evans, Gonnella, Marcynyszyn, Gentile, & Salpekar, ). Empirical support for this alternative model comes from a concept formation experiment wherein first graders ability to learn a concept differed by SES, but only when the results were contingent upon performance (Bresnahan & Blum, ). When performance feedback was random, task performance was equally low suggesting that, regardless of household SES, if the situation is chaotic and unpredictable, both groups did poorly.…”
Section: Poverty and Task Persistencementioning
confidence: 99%
“…Older studies on children's acquisition of new associative rules using operant conditioning paradigms showed that high-SES children can be led experimentally to perform similarly to low-SES children when they are preexposed to a high degree of random "chaotic" reinforcement. 48 Very recent reports confirm that low-SES children show less cognitive flexibility than their high-SES counterparts. 49 The latter findings demonstrate that uncertainty can directly affect cognitive flexibility, and ultimately, decision making.…”
Section: Internal Factorsmentioning
confidence: 99%
“…With reference to learning, these children seem to form a strong association that has not been explicitly instructed or reinforced, and then later struggle to engage cognitive flexibility by identifying new associations. Older studies on children's acquisition of new associative rules using operant conditioning paradigms showed that high‐SES children can be led experimentally to perform similarly to low‐SES children when they are preexposed to a high degree of random “chaotic” reinforcement . Very recent reports confirm that low‐SES children show less cognitive flexibility than their high‐SES counterparts .…”
Section: Internal Factorsmentioning
confidence: 99%